HUBUNGAN BERAT BAYI LAHIR RENDAH DENGAN KEJADIAN IKTERUS NEONATORUM DI RSUD PANEMBAHAN SENOPATI BANTUL - Siti Hajar, Neni; Isti Antari; Mifathul Mizan, Dian (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Icterus is one of clinical phenomenon that often found in the newborn baby. It can be occured because high amount of erythrocytes, short time live of erythrocytes, and immature function of hepatic. Icterus can be affected by some factors such like low birth weight <2500 gr, gestation time <36 weeks, asphyxia history, hypoxia, infection, head trauma, acute breath syndrome, hypoglicemic, hypercarbia and hemolysis that caused by blood incompatibility The aim of this study was to know the relationship between low birth weight with icterus case in RSUD Panembahan Senopati Bantul at 2015. This study used case control design with retrospective approach. The sample were all baby aged 2-7 days with physiological icterus and non physiological icterus. This study used systematic random sampling. Data analysis in this study used chi square test. According to the chi-square test, obtained result there was a significant relationship between low birth weight with an incidence of neonatorum icterus in RSUD Panembahan Senopati Bantul at 2015 with significant value < 0.000 (P value < 0,05) Keyword : Icterus, low birth weight, neonatorum, hyperbilirubin